2023
DOI: 10.1002/mco2.288
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the p53 signaling pathway in cancers: Molecular mechanisms and clinical studies

Abstract: Tumor suppressor p53 can transcriptionally activate downstream genes in response to stress, and then regulate the cell cycle, DNA repair, metabolism, angiogenesis, apoptosis, and other biological responses. p53 has seven functional domains and 12 splice isoforms, and different domains and subtypes play different roles. The activation and inactivation of p53 are finely regulated and are associated with phosphorylation/acetylation modification and ubiquitination modification, respectively. Abnormal activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 424 publications
0
5
0
Order By: Relevance
“…When TRIAP1 is overexpressed, it can impede the activation of APAF1/apoptosome, consequently blocking apoptosis in cancer cells. This inhibition of programmed cell death contributes to the advancement of cancer and its progression [48,49]. Future studies should confirm the downregulation of miR-5-7p and hence of TRIAP1 in the synergism of poziotinib and olmutinib.…”
Section: Discussionmentioning
confidence: 91%
“…When TRIAP1 is overexpressed, it can impede the activation of APAF1/apoptosome, consequently blocking apoptosis in cancer cells. This inhibition of programmed cell death contributes to the advancement of cancer and its progression [48,49]. Future studies should confirm the downregulation of miR-5-7p and hence of TRIAP1 in the synergism of poziotinib and olmutinib.…”
Section: Discussionmentioning
confidence: 91%
“…p53, a well-researched suppressor of tumor growth, plays a crucial role in initiating various biological responses. Its abnormal activation has a strong connection to the onset and progression of cancer ( Huang, 2021 ; Shen et al, 2023 ). Yang et al (2013) observed an upregulation of p53 expression and its downstream genes, p21 WAF1 and Bax, upon exposure of oral cancer cells to vitexin.…”
Section: Regulation Of Hawthorn On Anticancer Signaling Pathwaysmentioning
confidence: 99%
“…The early-identified p53-regulated genes coded for proteins promoting apoptosis, cell cycle arrest and DNA repair. However, as many more genes directly activated by p53 have been discovered, it was realized that p53 regulates wide spectrum of biological functions including metabolism, aging, angiogenesis, immunity, and more [1][2][3]. The p53 binds as a tetramer to its response element (RE) RRRCWWGYYYRRRCWWGYYY (R -A or G, Y -C or T, W -A or T) consisting of two decameric half sites divided further into four pentameric quarter sites (RRRCW or WGYYY).…”
Section: Introductionmentioning
confidence: 99%
“…This arrangement allows for some flexibility in the selection of p53 binding sites, which sometime can deviate from the consensus sequence [4]. 2 Recently, we published the transcriptomic data showing changes in gene expression in A549 lung cancer cell line exposed to actinomycin D and nutlin-3a (henceforth abbreviated to A+N) [5]. Earlier, we noticed that these two substances synergize in activation of p53 and in activation of some p53-regulated genes [6,7].…”
Section: Introductionmentioning
confidence: 99%